Significance of Late Devonian - Middle Carboniferous ages of hydrothermal sulphides and sericites from the Urals Volcanic-Hosted Massive Sulphide deposits - Tessalina, Svetlana; Jourdan, Fred; Belogub, E. (2017)
Formation of the Urals Volcanic-Hosted Massive Sulphide (VHMS) deposits is considered to be related with the intra-oceanic stage of the island arc(s) development in Late Ordovician – Middle Devonian time (ca. 460–385 Ma) based on the biostratigraphic record of ore-hosting sedimentary rocks. However, the known radiometric ages of ore hosting volcanics are very limited. Here we present direct dating results of sulphide mineralisation from the Yaman-Kasy and Kul-Yurt-Tau VHMS deposits using Re-Os isotope systematics showing similar mineralisation ages of 362 ± 9 Ma and 363 ± 1 Ma. These ages coincide with the previous Re-Os dating of the Alexandrinskoe (355 ± 15 Ma) and Dergamysh (366 ± 2 Ma) VHMS deposits. This Late Devonian (Famennian) age corresponds to the late stage of the ‘Magnitogorsk arc – Laurussia continent’ collision event and coincides with a beginning of large scale subduction-related granitoid magmatism. The younger mineralisation age relative to the biostratigraphic ages of host rocks is interpreted as one of the latest episodes of the multi-stage history of VHMS deposits development. Ar-Ar ages of sericites from metasomatic rocks of Barsuchi Log and Babaryk deposits show even younger ages clustering around 345 Ma, and testify another late hydrothermal event in the history of the Urals VHMS deposits.